Környezet és humántudomány: Az Environmental Humanities alapvetéseiről, céljairól, kiemelt kutatásairól röviden - Vincze, Richárd (Studia Litteraria, 2023)
Environmental Humanities has emerged as a discipline that seeks to explore aspects of ecological relations that have not been analysed (or are not possible to be analysed) by the natural sciences. The enquiry carried out in this particular field must be done by using the toolkit of the humanities in order to gain a better understanding of the current ecological problems. The paper aims to provide an overview of this field of research with special attention to exploring its historical antecedents and presenting its basic philosophical concepts. It also identifies the most important publications of the field and refers to textbooks, studies, and the system of journals. is introductory study tries to open up the discourse on the possibilities offered by the humanities that can contribute to solving (or soothing) the above mentioned environmental issues.